PEMANFAATAN CERITA RAKYAT SEBAGAI ALTERNATIF BACAAN BAGI ANAK - Siti Anafiah (Universitas Sarjanawiyata Tamansiswa, 2015)
Â Abstract:folkloreis astorypassed downfrom generation to generation, spreadthrough word ofmouth, andare anonymous. Folkloreis not aprivate property, butbelongs tothe community. The presence offolklorebringmanypositive benefitsto thechild. Benefits offolkloreincludeholisticdevelopment, cognitive, moral, language, andsocial. Folklorecanbe an alternativereadingtochildren, as long asparentscanselecta childreadingand provide insight intothe folklorethattheyread. It should be notedalsoonthe ageandinterests of childreninfolklorethatnotallfolkloreis suitableforallagelevelreaders, sodepending on the contentsandcomplexityofthe story.Â